Strategies for protecting senior citizens against online banking fraud and scams: a systematic literature review - Abdullah, Rusli; Khatiman, Muhammad Nur Aqmal; Mohd Zukry, Muhammad Amirrul Alhafiz (Little Lion Scientific, 2024)
This systematic literature review examines the need for strong strategies to protect seniors from online banking fraud and scams. The demographic's increased use of digital banking platforms due to the COVID19 epidemic has increased their cyber risk. This study identifies and evaluates multifaceted strategies to improve digital literacy, create user-friendly digital banking interfaces, enact and enforce strict regulatory frameworks, and encourage senior citizens to use electronic banking post-COVID-19. Digital literacy empowers seniors by helping them navigate online banking platforms securely and spot scams. This requires operational proficiency, cybersecurity knowledge, and threat identification and response. Online banking platforms must be user-friendly. For seniors with various digital skills and physical limitations, straightforward and easy-to-use interfaces can reduce the risk of fraud. This comprises simplifying transaction processes, providing clear instructions, and providing customized support. Seniors using online banking need regulatory frameworks to protect their financial interests and privacy. This evaluation assesses the effectiveness of current fraud and scam laws and practices and the need for improvements to address senior folks' special vulnerabilities. It shows how technology and law interact, emphasizing that regulatory authorities must adapt to digital changes to ensure comprehensive protection. Seniors have adopted e-banking due to the COVID-19 epidemic, which forced a move to digital platforms for many daily activities, including banking. Seniors face a variety of online hazards, yet this transition offers convenience and accessibility. Trust-building, education, and support services are crucial to helping this generation adopt e-banking, according to the analysis. According to this analysis, older folks need a multi-pronged cybersecurity approach that includes technological, educational, and regulatory components to improve their online banking experience and safeguard them from fraud and scams.